DABCO-catalyzed one-pot three component synthesis of dihydropyrano[3, 2-c]chromene substituted quinazolines and their evaluation towards anticancer activity. Issue 16 (15th August 2016) - Vodnala, Sumathi; Bhavani, A.K.D.; Kamutam, Ramakrishna; Naidu, V.G.M.; Promila; Prabhakar, Ch.
Graphical abstract: The novel carbon–carbon linked dihydropyrano[3, 2- c ]chromene substituted quinazolines were achieved via DABCO induced Knoevenagel–Michael addition reaction and resulting derivatives were evaluated towards anticancer activity. Abstract: A facile DABCO promoted one-pot three component synthesis of a new series of C–C linked bis-heterocycle containing dihydropyrano[ c ]chromene as highly fused oxa -heteryl group at C-2 position of quinazoline was developed. Quinazoline-2-carbaldehyde, substituted 4-hydroxycoumarin and ethyl cyanoacetate were used as key components in the Knoevenagel–Michael addition reaction to get the titled compounds. These compounds were screened for anti-cancer activity against the breast cancer cell lines of MDA-MB 231, and MDA-MB 453.